Efeito das técnicas de esmerilhamento e inversão de sentido nas propriedades de soldas subaquáticas molhadas - Gabriel Mendes de Almeida Carvalho (2017)
The structures used in the offshore segment, such as ships and platforms, are designed to withstand the most diverse loads, remaining intact and above all safe. In order to meet these needs for longer, it is necessary that the maintenance performed on them maintain the mechanical properties required. For economic reasons, the maintenance of these structures is almost always carried out offshore. Wet Welding with Coated Electrode (UWW-SMAW) due to its low cost in relation to other processes, its versatility in work and already achieving goodquality results has been widely used. In spite of the improvements achieved in recent years, mainly on the quality of the deposited metal, there are still problems in maintaining the mechanical properties in the proper values of the "welding region". One of the main problemsis the loss of ductility of heated regions adjacent to the weld or the heat-affected zone (HAZ). Due to the rapid cooling inherent in the wet process, a microstructure of high hardness and low toughness is generated. A possible alternative for improving the toughness in these regions is the application of a Post Weld Heat Treatment (PWHT) as already studied in processes out of water, however the application of a PWHT sometimes becomes impractical and difficult to implement in the underwater environment. One alternative of achieving improvements inmultipass weld properties may be the use of the heat itself from subsequent passes, promoting the tempering of hardened regions and thus, reaching suitable levels of hardness. In this work is studied the effect of two techniques and combinations of them during underwaterwelding without PWHT, to control the hardness of HAZ wet welds multipasses. One of the techniques used was grinding the weld after each weld pass deposited, always leaving 1mm of reinforcement. The other technique used was the inversion in the sense of welding to eachdeposition layer. For the study a bevel was developed with a value close to the diameter of the electrode used and with the parallel walls, so that the deposition was more behaved, also reflecting a better positioning of the HAZ to be evaluated. The material chosen was SAE 1045 steel, because it can be hardened, presenting regions of high hardness when cooled rapidly. The electrode used was the E 6013 varnished for underwater welding. All welds were produced i a hyperbaric chamber adapted to simulate welds at depths. The welds were made at a pressure equivalent to 10 meters deep. The results showed that when no technique is applied, internal HAZ points present regions of high hardness where heat from subsequent passes is not sufficient to promote adequate tempering of the material. However when using the grinding technique, removing part of the reinforcement, the heat is better utilized and the tempering achieved promotes softening of all extension of the ZTA, leaving values of hardness acceptable and below the limitsestablished by norm. On the other hand, no improvement has been noticed when using the inversion technique in the welding direction.